(untitled) (Global Journal of Science Frontier Research, 2023)
Due to the sanitary context experienced during the COVID-19 pandemic in the years 2020 and 2021 digital platforms as well as virtual learning environments such as Google Meet and Google Classroom became the main communication tools between students and the teacher In this scenario advancements in the use of digital and multimedia tools contributed to building a range of possibilities for the teaching and learning process Linked to this the utilization of gamified digital platforms can make tasks more stimulating and enjoyable resulting in increased engagement interaction and emotions while also promoting the integration of technologies into the teaching and learning process The gamified digital platform Classcraft designed for education offers an approach that engages students by combining elements of role-playing games RPGs with the educational environment creating an immersive and interactive experience